Faunistic composition of hymenopteran parasitoids in cultivation of Eucalyptus urophylla S.T. blake and adjacent areas of Seasonal Semi-deciduous Montana forest situated in the Semi-arid State of Bahia, Brazil - Paula, Rita de Cássia Antunes Lima de; Silva, Jennifer Guimarães; Fernandes, Daniell Rodrigo Rodrigues; Moreira , Aldenise Alves; Dall’Oglio, Onice Teresinha; Silva Junior, Juvenal Cordeiro; Pérez-Maluf, Raquel (EntomoBrasilis, 2022)
Hymenopteran parasitoids are insects that play a fundamental role in ecosystems as they reduce the population density of insects that are considered pests in monocultures. However, little is known about the fauna in association to the eucalyptus trees in comparison to adjacent native vegetations. Therefore, this study was aimed to determine the fauna of parasitoid wasps that occur in a commercial plantation of Eucalyptus urophylla S.T. Blake, as well as in native forest and capoeira environments in the plateau of Conquista, Bahia, a semiarid region of Bahia. The study was conducted for two consecutive years with monthly monitoring using five Malaise traps. The collected insects were sorted and identified at the family level. The faunal indices referring to the families of each area were studied by evaluating the frequency, species richness, shannon diversity and equitability. In total, 5,899 individuals were collected, which were distributed in 24 families and eight superfamilies. The most abundant families were Braconidae, Ichneumonidae and Bethylidae. Capoeira and eucalyptus trees showed greater similarity and equitability when compared to the rest of the forest. Given the diversity of Hymenopteran parasitoid families found in the area, it was concluded that the maintenance of native vegetation environments is important, even at the initial stage of succession.